Influence of stocking density on growth performance and welfare of juvenile tilapia (Oreochromis niloticus) in cages - Costa, A. A. P.; Roubach, R.; Dallago, B. S. L.; Bueno, G. W. [UNESP]; McManus, C.; Bernal, F. E. M. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2017)
Intensification of tilapia production can cause negative implications on performance and welfare of fishes. Thus, it is essential to determine a correct density for optimal production. This study aimed to evaluate performance and animal welfare of juvenile Nile tilapia with an initial weight average of 30g (+/- 2.70) reared using three different stocking densities in floating net-cages. Fish were fed three times a day with feed containing 32% crude protein during 74 days. The experimental design was completely randomized with 3 treatments (250 fish/m(3), 350 fish/m(3) and 450 fish/m(3)) and 4 replicas. The physical chemical parameters of water were monitored throughout the experiment. Increase in stocking density caused a decrease in the final weight of fish, weight gain, daily weight gain, standard length and survival, as well as an increase in feed conversion. However, higher densities seem to reduce the effect on weight variation. There was no influence of stocking density on final biomass, blood glucose and serum cortisol concentrations. Therefore, the increase of stocking density compromised development and survival of fish, but did not influence the physiological parameters of stress. Thus, treatment with 250 fish/m(3) was shown to be the most suitable for fish performance.
Keywords: animal welfare; aquaculture; biomass; cortisol; stress